Penerapan Terapi Murottal dan Bermain Terapeutik dalam Asuhan keperawatan pada Pasien Anak Leukemia Limfoblastik akut (ALL) dengan Ansietas di Ruangan Kronis Irna Anak RSUP Dr. M. Djamil Padang - Pangesti, Nindika Ario; Ilda, Zolla Amely (Jurusan Keperawatan Mandiri Poltekkes Kemenkes Padang, 2024)
Leukemia is the most common type of cancer in children. Long and repeated treatment periods cause children to experience hospitalization which has a psychological impact. One of the psychological impacts that children most often experience is anxiety. Anxiety needs to be anticipated, controlled and overcome so that the patient's quality of life remains optimal. One way is murottal therapy and therapeutic coloring play. Dr. Dr. Hospital's medical record data. M. Djamil Padang, recorded 169 cases of leukemia in 2022. The research aims to apply murottal therapy and therapeutic play (coloring) in the care of pediatric patients with Acute Lymphoblastic Leukemia (ALL) with anxiety in the chronic room of IRNA Children's Hospital Dr. M. Djamil Padang. Descriptive research design with a case study approach in the pediatric IRNA chronic room from 15 May - 3 June 2023. The research population was all 8 pediatric patients with ALL. The sample was 2 participants with ALL who met the criteria. The results of the research on the second participant showed a difference in anxiety levels before and after murottal therapy and therapeutic play (coloring) from anxiety level 5 (very anxious) to 2 (happy). Advice to nurses in the children's room to carry out Murottal therapy and therapeutic play for leukemia children who experience anxiety due to hospitalization.